ইসলামের দৃষ্টিতে বিশ্ব বাণিজ্য সংস্থার কার্যক্রম: একটি পর্যালোচনা | Activities of World Trade Organization: A Brief Analysis (ইসলামী আইন ও বিচার | Islami Ain O Bichar, 2023)
Trade regulations are one of the most widely discussed issues in the fast paced globalized world of the 21st century. In this current economic system each nation is heavily reliant on export import trade for economic progress. As such each country is interested in promulgating trade regulations which promote and preserve their national interest which may be in conflict with the interests and welfare of other nations. With this in view and to promote fair participation in trade, the World Trade Organization (WTO) works with all nations by establishing close cooperation and coordination at the international level. This article highlights the issues related to the national interests of developing nations in light of trade regulations set by WTO and also sheds light on its compatibility with Islamic Law. The article embarks upon an analytical and comparative discussion on the principles of WTO in light of Islamic Law. The article demonstrates that the principles and trade agreements of World trade organization are not in conflict with Islamic laws and would also bring about better results if the principles of WTO are reorganized according to Islamic Laws.সারসংক্ষেপ: একুশ শতকের সমস্যাসংকুল বিশ্বায়নে বাণিজ্যনীতি একটি অতিগুরুত্বপূর্ণ ইস্যু। বাণিজ্যনির্ভর অর্থ ব্যবস্থায় প্রত্যেকটি দেশই আমদানি-রপ্তানি নির্ভর। এ কারণে প্রতিটি রাষ্ট্রই নিজ নিজ স্বার্থ সংশ্লিষ্ট বাণিজ্যনীতি প্রণয়ন করতে গিয়ে অনেক ক্ষেত্রে অন্য রাষ্ট্রের স্বার্থক্ষুণেœর কারণ ঘটাতে পারে। এ লক্ষ্যে বিশ্ব বাণিজ্য সংস্থা আন্তর্জাতিক পরিসরে বিভিন্ন দেশের মধ্যে সমন্বয়ের মাধ্যমে সুসম্পর্ক স্থাপন ও বাণিজ্যে সকলের অংশগ্রহণ নিশ্চিতকরণের প্রয়াস অব্যাহত রেখেছে। বক্ষ্যমাণ প্রবন্ধে বিশ্ব বাণিজ্যসংস্থার চুক্তির আলোকে অনুন্নত দেশের সুযোগ-সুবিধা এবং ইসলামী আইনের সাথে তার সামঞ্জস্য বিধানের বিষয়ে আলোচনা করা হয়েছে। এতে বিশ্ব বাণিজ্য সংস্থার মূলনীতির সাথে ইসলামী আইনের দৃষ্টিকোণের তুলনামূলক ও বিশ্লেষণধর্মী পর্যালোচনা করা হয়েছে। প্রবন্ধ থেকে প্রমাণিত হয়েছে যে, ইসলামী আইনের মূলনীতি ও বিশ্ব বাণিজ্যসংস্থার অঙ্গীকার বা চুক্তিসমূহের মধ্যে বৈপরীত্য নেই, বরং ইসলামী আইনকে সামনে রেখে উক্ত নীতিমালা পুনর্গঠিত হলে অধিক ফলপ্রসূ হওয়ার সম্ভাবনা রয়েছে।